REGIONAL ECONOMIC INTERESTS IN UZBEKISTAN’S FOREIGN POLICY - Abdujamol Kholbekov (International Scientific and Current Research Conferences, 2023)
The article emphasizes the orientation of President Shavkat Mirziyoyev to Central Asia in his foreign policy strategy, prioritizing the region for Uzbek diplomacy through concrete actions and results, as well as military-political security, trade, and economic cooperation in the region.